Advanced phase shifting algorithms: development and evaluation - Chen, Yuchi (Nanyang Technological University, 2022)
Phase extraction is extremely important in optical metrology, for which, many phase-shifting algorithms who are either with known phase shifts and based on simple triangular identities (abbreviated as kPSA) or with unknown phase shifts and based on advanced techniques (abbreviated as uPSA) have been developed; followed by numerous development and evaluation studies. However, these works are mainly for the kPSAs, and only few are for the uPSAs. Therefore, in this thesis, we focused on the following issues of the existing uPSAs, including (i) the unclear restrictions, (ii) the unoptimized accuracy, (iii) the unpredictable performance, and (iv) the unaccelerated speed; and proposed multiple novel uPSAs who have superior accuracy, fewer restrictions, better predictability and faster speed. Meanwhile, we also compared the uPSAs with the kPSAs to showcase the merits of both kPSAs and uPSAs; and proposed a good-performing and restriction-free hybrid kPSA-uPSA by combining the merits of both categories.